2021
DOI: 10.1186/s12984-021-00931-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the usability of wearable devices to measure gait and physical activity in chronic conditions: a systematic review

Abstract: Background The World Health Organisation’s global strategy for digital health emphasises the importance of patient involvement. Understanding the usability and acceptability of wearable devices is a core component of this. However, usability assessments to date have focused predominantly on healthy adults. There is a need to understand the patient perspective of wearable devices in participants with chronic health conditions. Methods A systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 81 publications
(222 reference statements)
1
21
0
Order By: Relevance
“…Evidently, the systems tend to be increasingly simple, user-friendly, and less intrusive; so the individual can carry out their normal tasks throughout the day, without the system interfering. In this sense, the places identified through different devices, allowed the user to quickly forget their use, enabling monitoring and evaluation in a real context without feeling the pressure of being evaluated, avoiding the modification of values [ 21 , 26 , 27 , 28 , 31 , 48 , 49 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the systems tend to be increasingly simple, user-friendly, and less intrusive; so the individual can carry out their normal tasks throughout the day, without the system interfering. In this sense, the places identified through different devices, allowed the user to quickly forget their use, enabling monitoring and evaluation in a real context without feeling the pressure of being evaluated, avoiding the modification of values [ 21 , 26 , 27 , 28 , 31 , 48 , 49 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…33,37,69,75 Wearable devices are being deployed to measure characteristics of gait and physical activities across a broad range of health conditions, 35,65,66 but the assessment of usability is very limited. 33 Searches using combinations of ''usability'', ''head impact'', ''on-field'', and ''concussion'' identified few papers that reported on the system usability of head acceleration devices. Tierney et al.…”
Section: On-field Deployment Logistics and Best Practicesmentioning
confidence: 99%
“…Wearable head acceleration measurement devices intersect with many disciplines, including ‘Digital health’ and ergonomics/human factors, and are not limited to biomechanics, sports science, or medicine. 33 , 37 , 69 , 75 Wearable devices are being deployed to measure characteristics of gait and physical activities across a broad range of health conditions, 35 , 65 , 66 but the assessment of usability is very limited. 33 Searches using combinations of “usability”, “head impact”, “on-field”, and “concussion” identified few papers that reported on the system usability of head acceleration devices.…”
Section: On-field Deployment Logistics and Best Practicesmentioning
confidence: 99%
“…Think-alouds and qualitative interviews were the most frequently used methods in the usability testing of eHealth solutions [11]. For patients with PD specifically, usability assessments have mainly relied on questionnaires as well as adherence monitoring and mostly reported positive results for sensor systems and smartphone/tablet apps [12][13][14][15]. Although mixed methods approaches have become more common recently, there is substantial heterogeneity in the methods, and only a minority of studies focused specifically on the usability.…”
Section: Introductionmentioning
confidence: 99%
“…Although mixed methods approaches have become more common recently, there is substantial heterogeneity in the methods, and only a minority of studies focused specifically on the usability. In the broader context of chronic conditions, a recent systematic review concluded that the usability of wearable devices is poorly measured and reported [ 15 ]. Furthermore, there is no consensus regarding the methodology to assess usability in older adults, even though investigations about the sensitivity of different methods have been explicitly recommended [ 16 ].…”
Section: Introductionmentioning
confidence: 99%